home solving equations with fractions methods for solving quadratic equations solving equations solving equations linear equations solving equations solving equations with variables on each side solving equations linear equations solving linear equations steps for solving linear equations solving equations with variables on each side solving quadratic equations solving equations solving equations steps for solving linear equations quadratic equations writing linear equations solving equations solving rational equations solving equations solving equations solving systems of equations using elimination solving linear equations solving equations solving quadratic equations methods for solving quadratic equations solving equations solving equations equation solving resources
Try the Free Math Solver or Scroll down to Tutorials!

 Depdendent Variable

 Number of equations to solve: 23456789
 Equ. #1:
 Equ. #2:

 Equ. #3:

 Equ. #4:

 Equ. #5:

 Equ. #6:

 Equ. #7:

 Equ. #8:

 Equ. #9:

 Solve for:

 Dependent Variable

 Number of inequalities to solve: 23456789
 Ineq. #1:
 Ineq. #2:

 Ineq. #3:

 Ineq. #4:

 Ineq. #5:

 Ineq. #6:

 Ineq. #7:

 Ineq. #8:

 Ineq. #9:

 Solve for:

 Please use this form if you would like to have this math solver on your website, free of charge. Name: Email: Your Website: Msg:

When fractions occur we can sometimes transform the equation to one that does not involve fractions.

Example

Find the solution to the equation

(4 x/ 5) - (7 / 4) = ( x/ 5) + ( x/ 4) .

Solution

The least common multiple of the denominators in the equation is 4 × 5 = 20 and we proceed as follows:

16 x - 35 = 4 x + 5 x

16 x - 35 = 9 x

adding 35 to both sides and subtracting 9 x from both sides leads to

7 x = 35 so x = 5 is the solution to the equation .

Exercise

Find the solution to each of the following equations.

(a) 5 x - 6( x - 5) = 2( x + 5) + 5( x - 4)

(b) ( x + 15)( x - 3) - ( x - 6 x + 9) = 30 - 15( x - 1)

(c) ( x - 2) / 2 + ( x + 10) / 9 = 5

Solution

(a)

5 x - 6( x - 5) = 2( x + 5) + 5( x - 4)

5 x - 6 x + 30 = 2 x + 10 + 5 x - 20

- x + 30 = 7 x - 10

30 = x + 7 x - 10

30 = 8 x - 10

30 + 10 = 8 x

8 x = 40

x = 5

(b) First, using FOIL , we expand

( x + 15)( x - 3) = x - 3 x + 15 x - 45 = x + 12 x - 45

Now we have

( x + 15)( x - 3) - ( x14 2 - 6 x + 9) = 30 - 15( x - 1)

x + 12 x - 45 - x + 6 x - 9 = 30 - 15 x + 15

18 x - 54 = 45 - 15 x

18 x + 15 x - 54 = 45

33 x - 54 = 45

33 x = 45 + 54

33 x = 99

x = 3

(c) This time we multiply both sides by 2 × 9 .

9( x - 2) + 2( x + 10) = 90

9 x - 18 + 2 x + 20 = 90

11 x + 2 = 90

11 x = 88

x = 8

Quiz

Which of the following is the solution to the equation (x - 4)/7 = (x - 10)/5 ?

(a) 11 (b) - 10 (c) 19 (d) 25

Solution:

The highest common factor of the denominators is 5 × 7 = 35 . Multiplying both sides of the equation by this

5( x - 4) = 7( x - 10)

5 x - 20 = 7 x - 70

5 x - 20 + 70 = 7 x - 70 + 70

5 x + 50 = 7 x

50 = 7 x - 5 x = 2 x

x = 25

so that x = 25 is the solution. This can be checked by putting this value into the original equation and showing that each side will have the value 3 .